Penolakan Permohonan Itsbat Nikah Oleh Hakim di Pengadilan Agama Kelas 1A Padang - Aldianto Ilham; Zainal Azwar (Al-Qisthu: Jurnal Kajian Ilmu-Ilmu Hukum, 2022)
This article explains the application for marriage certificate which was rejected by the Religious Court. This research is focused on what are the reasons that lead to the rejection of the application and what are the efforts, both legal and non-legal, made by the applicant whose application was rejected. This study uses a normative-empirical legal research method with a judicial case study approach. Data was collected from documents and from informants through interviews. The source of the document is in the form of a request document and a judge's decision at the Class 1A Padang Religious Court; while interviews were conducted with applicants whose applications were rejected, from officials at the Office of Religious Affairs, and from officers from the Population and Civil Registry Service. This study shows that there are five reasons for rejection by the Religious Court Class 1A Padang of filing a marriage certificate application, namely because the applicant is still married to another person, the guardian who is marrying is invalid, the marriage is still under public, witnesses cannot provide information that can accepted, and the applicant was not present at the trial. The efforts made by the applicant whose application was rejected were only in the form of non-legal efforts. Of all the cases examined, none of the applicants made further legal efforts in the form of cassation due to their ignorance. They made other efforts in the form of re-marriage at the Office of Religious Affairs and determining the origin of the children.